PENDUGAAN KARBON TERSIMPAN TEGAKAN AKASIA (Acasia mangium Wild.) UMUR 10 TAHUN DI HUTAN TANAMAN INDUSTRI PT KORINTIGA HUTANI, PROVINSI KALIMANTAN TENGAH : Vieve Sanjaya Geruntung Nyahu - JHT, Admin (Jurnal Hutan Tropika, 2016)
ABSTRACT Forest role as climate stabilizer may be realized due to its ability to control world climate change caused by the rising concentrations of greenhouse gases. Carbon dioxide (CO2) is one of greenhouse gas with very rapid increase in its concentration. An effort has been taken to suppress the increase in CO2 is by controlling the concentration of carbon through advancement of carbon absorption program, where organic carbon as a result of photosynthesis will be stored in the biomass of forest stands or woody trees. Acacia (Acacia mangium Wild.) is one of fast growing species and is often used as a staple crop in forest plantation (HTI). The purpose of this study is to determine the potential of carbon stock by diameter class, predict carbon stocks and aerial CO2 absorption by Acacia trees in forest plantation area of PT Korintiga Hutani, Lamandau District, Central Kalimantan Province. The study was carried out in PT Korintiga Hutani plantation forest and took Acacia stands aged years as its object. Biomass measurement of Acacia stands was done indirectly using allometric formula proposed, whereas biomass of under the plant, woody and litter necromass was allegedly using the direct method. Carbon of Acacia stands, woody necromass, undergrowth and litter were determined using the formula, where 46% of biomass is carbon content. Lastly, the amount of carbon dioxide absorbed by Acacia stands was predicted using the formula. The results show that the average carbon stock by diameter class of Acacia stands aged 10 years are 109.66 tons/ha, respectively. Carbon stocks of undergrowth, woody necromasa and litter on the location of Acacia stands aged 10 years are 1.42 tons/ha, 0.15 tons/ha and 3.00 tons/ha, respectively. Total carbon stocks on the location of Acacia stands aged 10 years are 114.23 tons/ha. In the meantime, CO2 absorbability of Acacia stands aged 10 years amounted to 402.46 tons/ha with the rate of CO2 uptake increased by 40.25 tones/ha/year, respectively. Keywords: Acacia stands, carbon stock, forest plantation, carbon dioxide.